Vitamin D categories and postpartum thyroid function in women with hypothyroidism - Chen, Yanrong; Zhang, Sijing; Hu, Lingling; Dong, Lun; Liu, Qiuhong; Liu, Yunting; Cheng, Wei; Liu, Dongfang; Yang, Gangyi; Li, Ke (Frontiers in Nutrition, 2022)
Objective To analyze the related factors of the postpartum thyroid function in women with overt hypothyroidism (OH)/subclinical hypothyroidism (SCH) and explore the effects of vitamin D categories. Methods Thyroid hormones, thyroid autoantibody, and serum 25OHD levels were continuously recorded from the first trimester of pregnancy (T1) to the 12th postpartum month. Logistic regression analysis and Cox regression analysis were used to screen the related factors of postpartum thyroid function, and the Latent Class Growth Model was performed to analyze the trajectory characteristics of serum 25OHD levels. Results Totally, 252 pregnant women with OH/SCH were enrolled in the study. In the 12th month postpartum, 36.5% of the patients improved thyroid function, 37.3% continued hypothyroidism, and 26.2% developed thyroid dysfunction. Vitamin D sufficiency, positive TPOAb, and positive TgAb in T1 were independent prognostic factors of postpartum thyroid function. Vitamin D sufficiency in T1 was illustrated as an independent factor of the improved postpartum thyroid function, but the protective effect for the developed postpartum thyroid dysfunction was only confirmed in TPOAb-positive patients. Cox regression analysis further confirmed the effects of vitamin D categories. Notably, the high-level 25OHD trajectory during pregnancy and postpartum could predict improved postpartum thyroid function and decrease the risk of developed postpartum thyroid dysfunction. Conclusion Appropriate vitamin D nutrition during pregnancy and postpartum may be beneficial to postpartum thyroid function.